From waste to relief: unlocking the potential for food rescue in low- and middle-income countries - Bodach, Susanne; Athukorala, Aruni Narmada; Wickramaarachchi, Hasintha (2023)
Food rescue has emerged as a promising approach to address the interrelated issues of food insecurity and food waste. According to the food waste hierarchy, the next best strategy after food waste prevention is to donate surplus food for human consumption. However, while some countries have well-established networks of charities and government support to promote surplus food donation and food rescue in most developing countries is often less structured and smaller in scale. To gain insights into the current landscape of food rescue, this study thoroughly examined existing food rescue operations and systems, mainly from the UK, Singapore, Malaysia, India, and the Philippines. The study also analysed several countries' food rescue policy environments to understand how an enabling environment can be created. A particular focus was set on food safety being a critical consideration when rescuing and donating surplus food. Simplified food safety guidelines, staff training, and adequate storage and transportation facilities are crucial to food safety. Effective partnerships between food rescue organizations, food businesses, government agencies, and other stakeholders are also critical to the success of food rescue efforts. The study found a need to develop such partnerships in developing countries, where they may be less established than in the Global North. To facilitate the development of an enabling environment for food rescue in low- and middle-income countries (LMICs), the study developed a set of templates, including relevant food safety guidelines, partnership contracts, and policy templates. These resources can serve as valuable tools for stakeholders in LMICs to promote and enhance food rescue efforts that can help address food insecurity and reduce food waste.